Remodelling work-integrated learning experiences of Grade R student teachers - Bouwer, M.; Venketsamy, R.; Bipath, K. (South African Journal of Higher Education, 2021)
There is a high demand by the Department of Basic Education (2011) to develop competent, flexible and knowledgeable teachers with bolstered attitudes and beliefs about their profession. Work Integrated Learning (WIL) is a crucial part in the Diploma in Grade R programme at a Private Higher Education Institution (PHEI) to prepare Grade R teachers. To prepare student teachers for the profession, they need quality experiences of WIL to apply their theoretical knowledge into authentic contextual situations. This study aimed to explore Grade R student teachers’ experiences of WIL and their ability to transfer their knowledge and experiences into practice. Purposeful sampling was used to identify four student teachers as participants for this study. A qualitative case study research design, using in-depth interviews, observations and documentation was conducted. Data was analysed thematically through the lens of the situated learning theory by Jean Lave and Etienne Wenger (1991). Findings showed that Grade R student teachers experienced positive and negative aspects associated with their WIL practice. Their experiences related to the need for remodelling the WIL experience, which would entail moving from the periphery to full participation in classrooms, at least in the final year of their diploma programme. The use of Community of Practices (CoPs) in a WIL model would enhance practical experiences. Collaborative, comprehensive and critically constructive discussions after lessons are taught during WIL, would mould future Grade R teachers to embrace their working careers with competence and confidence.